A Needs Analysis of Speaking Skills for Law Students at Islamic University of Riau - Tri Astuti, Missi; Novitri, Safriani; Haryadi, Octadino; Nazif Hibatullah, Fikri; Ikhsan Mal Putra, Fadilah (English Lecturers and Teachers Association (ELTA), 2025)
This study investigates the internal and external constraints faced by law students at the Islamic University of Riau in developing their English speaking skills. Employing a descriptive qualitative approach, data were collected through questionnaires administered to 37 students enrolled in the English for Law Students course during the 2023/2024 academic year. The findings reveal that internal barriers, particularly speaking anxiety (68%) and fear of making mistakes (62%), significantly hinder students’ oral proficiency. Externally, insufficient opportunities for speaking practice (62%) and learning materials that lack relevance to legal contexts (57%) also contribute to the challenges encountered. The study underscores the necessity for psychological support and pedagogical adjustments, recommending communicative and context-based teaching methods tailored to legal English. Such interventions aim to enhance students' confidence and speaking performance, preparing them for the demands of the global legal profession. This research highlights the multidimensional nature of language learning obstacles and calls for integrated strategies addressing both affective and contextual factors. Keywords : Analysis; Speaking Skills